Influence of Endodontic Access Cavity Design on Fracture Strength of Maxillary Incisors and Premolars and on Fatigue Resistance of Reciprocating Instruments - Spicciarelli, Valentina; Marruganti, Crystal; Marzocco, Dario; Martignoni, Marco; Ounsi, Hani; Grandini, Simone (Frontiers in Dental Medicine, 2020)
Introduction: The aim of this study was to compare the effect of two different access cavity designs on fracture strength of endodontically treated teeth and on cyclic fatigue resistance of Reciproc blue instruments. Methods: Forty (40) maxillary central incisor teeth and forty (40) upper first premolars were selected and divided into 4 groups (n=20/group): Group 1A, incisors prepared with conservative access cavity (CEC); group 1B, incisors prepared with traditional access cavity (TEC); group 2A, premolars prepared with CEC; group 2B, premolars prepared with TEC. After access cavity preparation, all teeth were endodontically treated, restored and then loaded to fracture. A total of 80 Reciproc blue R25 files were used for root canal shaping and then tested for cyclic fatigue. Normality of data distribution was evaluated by Kolmogorov-Smirnov test. Data were statistically analyzed by Independent T-test and the significance level was set at p<0.05. Results: No statistically significant differences in fracture strength were found between the two tested access cavities both for incisors (P=0.70) and premolars (0.422). Cyclic fatigue resistance of Reciproc blue R25 was significantly reduced in endodontically treated teeth with CEC (P < 0.001). Conclusions: Within the limits of the present in vitro study, CEC does not increase fracture strength of endodontically treated teeth in comparison to TEC. Conservative Endodontic Cavity causes more cyclic fatigue of Reciproc blue R25 than Traditional Endodontic Cavity.